Determination of crystal growth velocity - Kovač, Risto (Journal of Production Engineering, 1990)
Based on Kolmogorov kinetic equation of solidification (3), equation of energy conservation in a casting - die system (78) and general relation for normal growth of crystal (4), equation (27) which determines growth velocity of crystal, is given. This equation connects die and casting parameters and it is presented in analytical form. Using growth velocity of crystal W and undercooling Tkr-T ratio in temperature interval of crystallization, coefficient of growth velocity of crystal 1(0 is determined. In experimental way coefficient of heat transfer et between the casting and the die, and number of grains in structure is obtained. According to equilibrium diagram of Al-Cu alloy, using relative amount of solid fraction i and equilibrium temperature Tr, unidimensional parameter K3 is determined. According to presented equations, it can be seen that significant influence on changing of crystal growth speed W and coefficient of crystal growth velocity, has relative fraction of solid phase IP. Significant increasing of solid fraction IP at the beginning of solidification (when undercooling is quite small) has influence on changes crystal growth coefficient k (Fig.4.), and way of changing of crystal growth velocity as well (Fig.3.).